A NUMERICAL APPROACH FOR SOLVING BOUNDARY VALUE PROBLEMS FOR FRACTIONAL DIFFERENTIAL EQUATIONS USING SHANNON WAVELET. (2016) - CHANDEL, RAGHVENDRA SINGH; SINGH, AMARDEEP; CHOUHAN, DEVENDRA
No abstract available